2017
DOI: 10.3390/ijms18020305
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fibrotic Effect of Losartan, an Angiotensin II Receptor Blocker, Is Mediated through Inhibition of ER Stress via Up-Regulation of SIRT1, Followed by Induction of HO-1 and Thioredoxin

Abstract: Endoplasmic reticulum (ER) stress is increasingly identified as modulator of fibrosis. Losartan, an angiotensin II receptor blocker, has been widely used as the first choice of treatment in chronic renal diseases. We postulated that anti-fibrotic effect of losartan is mediated through inhibition of ER stress via SIRT1 (silent mating type information regulation 2 homolog 1) hemeoxygenase-1 (HO-1)/thioredoxin pathway. Renal tubular cells, tunicamycin (TM)-induced ER stress, and unilateral ureteral obstruction (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Recent studies have suggested the involvement of ER stress in renal fibrosis [23,32,33]. In the present study, we have provided substantial evidence to support a role of ER stress in post-AKI fibrosis.…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies have suggested the involvement of ER stress in renal fibrosis [23,32,33]. In the present study, we have provided substantial evidence to support a role of ER stress in post-AKI fibrosis.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, chronic ER stress can be pro-apoptotic and pro-inflammatory with loss of function: important new evidence links chronic ER stress with fibrotic disease [ 1 , [10] , [11] , [12] , [13] , [14] , [15] ]. ER stress can augment TGF-β signaling, whereas agents that reduce ER stress attenuate fibrosis [ 14 , [16] , [17] , [18] ]. In the kidney, ER stress affects both epithelial and fibroblast compartments and induces apoptosis, mesenchymal phenotype transition, and alters extracellular matrix (ECM) production by tubular epithelium: this is significant since tubular injury is a major determinant of progressive chronic kidney disease [ 11 , [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy of note that the implication and importance of SIRT1 in kidney-related diseases, such as diabetic nephropathy [ 26 , 32 , 33 , 34 ], acute and chronic kidney disease [ 19 , 35 , 36 ] or lupus nephritis [ 27 , 37 ] can be explained by its involvement in numerous pathways regulation. SIRT1 regulates the TGFβ/Smad and ERK1/2 pathways, also activates metalloproteinases and FOXO1 proteins and controls the NF-kB pathway [ 24 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%